First Principles Calculation of Protein–Protein Dimer Affinities of ALS-Associated SOD1 Mutants - Hsueh, Shawn C. C.; Nijland, Mark; Peng, Xubiao; Hilton, Benjamin; Plotkin, Steven S. (Frontiers in Molecular Biosciences, 2022)
Cu,Zn superoxide dismutase (SOD1) is a 32 kDa homodimer that converts toxic oxygen radicals in neurons to less harmful species. The dimerization of SOD1 is essential to the stability of the protein: Monomerization increases the likelihood of SOD1 misfolding into conformations associated with aggregation, cellular toxicity, and neuronal death in familial amyotrophic lateral sclerosis (fALS). The ubiquity of disease-associated mutations throughout the primary sequence of SOD1 suggests an important role of physico-chemical processes, including monomerization of SOD1, in the pathology of the disease. Here we use a first-principles statistical mechanics method to systematically calculate the free energy of dimer binding for SOD1 using molecular dynamics, which involves sequentially computing conformational, orientational, and separation distance contributions to the binding free energy. We consider the effects of two ALS-associated mutations in SOD1 protein on dimer stability, A4V and D101N, as well as the role of metal binding and disulfide bond formation. We find that the penalty for dimer formation arising from the conformational entropy of disordered loops in SOD1 is significantly larger than that for other protein-protein interactions previously considered; In the case of the disulfide-reduced protein this leads to an unstable bound complex. On the other hand, disulfide reduction in the apo protein appears to relieve strain and facilitate folding of the loops in the bound dimer. Somewhat surprisingly, the loop free energy penalty upon dimerization is still significant for the holo protein, in spite of the increased order induced by the bound metal cations. This resulted in a surprisingly modest increase in dimer binding free energy of only about 1.5 kcal/mol upon metallation of the protein, suggesting the most significant effects of metallation are on folding rather than dimer binding stability. The mutant A4V has an unstable dimer due to weakened inter-monomer interactions, manifested in the separation PMF. The mutant D101N has a stable dimer, due in part to an unusually rigid beta-barrel in the free monomer; D101N also exhibits anti-cooperativity in loop folding upon dimerization. These computational calculations are to our knowledge the most quantitatively accurate calculations of dimer binding stability in SOD1 to date.